Estudio de prefactibilidad para la exportación de fresa fresca desde Ibagué – Colombia hacia la ciudad de panamá - panamá (2021)
The present work; Prefactibility study for the export of fresh strawberry from Ibagué - Colombia to Panamá city - Panamá is based mainly on taking advantage of the existing commercial relations between Panamá and Colombia, in order to open new markets abroad with Colombian products, which are of a high level of quality and are cultivated by Colombian farmers.